2021
DOI: 10.1177/00238309211013865
|View full text |Cite
|
Sign up to set email alerts
|

To What Extent is Collocation Knowledge Associated with Oral Proficiency? A Corpus-Based Approach to Word Association

Abstract: This study examined the relationship between second language (L2) learners’ collocation knowledge and oral proficiency. A new approach to measuring collocation was adopted by eliciting responses through a word association task and using corpus-based measures (absolute frequency count, t-score, MI score) to analyze the degree to which stimulus words and responses were collocated. Oral proficiency was measured using human judgements and objective measures of fluency (articulation rate, silent pause ratio, filled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 97 publications
(186 reference statements)
1
10
0
Order By: Relevance
“…The finding that the present intervention led students to expand their MWE repertoires by adding strong collocations, including words from relatively low frequency bands, is noteworthy, because studies have shown that it is mastery of this kind of MWEs that is associated with advanced, native-like, proficiency (Bestgen, 2017;Durrant & Schmitt, 2009;Granger & Bestgen, 2014;Paquot, 2019;Saito, 2020;Uchihara et al, 2022;Yoon, 2016). It was acknowledged above that the formulaic density of the experimental group's essays was only moderately higher than the comparison group's in real terms.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The finding that the present intervention led students to expand their MWE repertoires by adding strong collocations, including words from relatively low frequency bands, is noteworthy, because studies have shown that it is mastery of this kind of MWEs that is associated with advanced, native-like, proficiency (Bestgen, 2017;Durrant & Schmitt, 2009;Granger & Bestgen, 2014;Paquot, 2019;Saito, 2020;Uchihara et al, 2022;Yoon, 2016). It was acknowledged above that the formulaic density of the experimental group's essays was only moderately higher than the comparison group's in real terms.…”
Section: Discussionmentioning
confidence: 78%
“…There is growing evidence of a close association between second language (L2) proficiency and learners’ knowledge of a wide range of conventional multiword expressions (MWEs). Knowledge of MWEs has been shown to benefit reading comprehension (Kremmel et al., 2017), speaking skills (Saito, 2020; Stengers et al., 2011; Tavakoli & Uchihara, 2020; Uchihara et al., 2022), and writing skills (Bestgen, 2017; Crossley et al., 2015; Granger & Bestgen, 2014; Paquot, 2019; Yoon, 2016). There is also growing recognition, however, that this dimension of language poses serious challenges for L2 learners (Durrant & Schmitt, 2009; Granger, 1998; Laufer & Waldman, 2011; Li & Schmitt, 2010; Nguyen & Webb, 2017), especially if acquisition of MWEs is left to the odds of incidental uptake (Boers, 2020).…”
mentioning
confidence: 99%
“…While Kahng (2020) has shed some light on the contribution of phrasal vocabulary size to UF, De included productive collocation knowledge as part of vocabulary knowledge, thereby obscuring the unique contribution of collocation knowledge to UF. In this context, two studies (Koizumi & In'nami, 2013;Uchihara et al, 2021) merit closer review since they estimated learners' collocation knowledge in association with their L2 UF performance, albeit without explicitly framing their studies within the CF-UF link framework. Koizumi and In'nami (2013) tested the predictive strength of vocabulary size, depth, and retrieval speed to L2 UF using SEM.…”
Section: Cognitive Processes Underlying Utterance Fluencymentioning
confidence: 99%
“…The SEM model demonstrated that the R 2 value was very small for speed fluency (.17) and repair fluency (.07) in study 1 and small to moderate for speed fluency (.46) and repair fluency (.11) in study 2. Uchihara et al (2021) measured collocation knowledge within a word-association paradigm for 40 Japanese university students. Frequency and association strength (MI and t-score) between the target word and the first and all responses were computed.…”
Section: Cognitive Processes Underlying Utterance Fluencymentioning
confidence: 99%
“…First, collocation knowledge has significant role in learning L2 (Rahimi & Momeni, 2012). Speaker who has good speaking fluency, they must be good in collocation knowledge (Uchihara et al, 2022). Secondly, Collocation L1 also influence collocation in L2, it reflects on writing skill.…”
Section: Introductionmentioning
confidence: 99%